Struktur pati beras (Oryza sativa L.) dan mekanisme perubahannya pada fenomena gelatinisasi dan retrogradasi - Fathma Syahbanu; Florensia Irena Napitupulu; Siska Septiana; Nisrina Fauziyah Aliyah (AGROINTEK, 2023)
Carbohydrates in rice (Oryza sativa L.) consist of starch (85-90 % of dry basis), pentose (2.0–2.5 %), cellulose, hemicellulose, and sugar (0.6–1.4 % of brown rice). High starch content in rice affects its physicochemical properties and nutrient content as well as the digestibility. Different starch characteristics are caused by the interaction between constituent compound in each structural level, both in microscopic and macroscopic levels. Hydrogen interactions between amylose and amylopectin can form crystalline and amorf areas, and continuously undergo the growth to form supramacromolecular structure (starch granule blocklets). The composition and interactions of several blocklets, both of large and small sizes, are the key of biopolymer interaction to form macroscopic structure: the whole starch itself. The aim of this review is to discuss the structural levels of rice starch and the mechanism of its changes in gelatinization and retrogradation. The review of this manuscript was performed using the “narrative review” method. The overall of starch characterization encompass structure, composition, and its molecular size which can be a determinant to its functional properties related to gelatinization and retrogradation.